Determinants of Farmer's Participation in Implementation Community Empowerment: A Case Study of Thematic Village in Indonesia - Agus Subhan Prasetyo; Annisa Firdauzi (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Farmer participation has been in the spotlight in agricultural socio-economy academia as a tool to induce sustainable agricultural development. Farmer participation should be present as a basic human need and human right. However, farmer participation is often hampered due to unequal power relations. This condition makes community empowerment programs often fail, and farmer participation becomes ineffective. The research aimed to analyze the influence of the determinants of farmer participation. The research location conducted was Wates Village, Semarang City, Central Java in July – September 2022. This study uses quantitative methods with SEM-PLS analysis tools and descriptive quantitative. A purposive sampling method was used for Respondents, with total respondents of 125 farmers. Observations and Interviews were used in data collection using questionnaires. The data were analyzed using descriptive analysis and scored using a Likert scale and Structural Equation Modelling (SEM) method. Two variables in this research showed no significant direct effects between individual characteristics and the intensity of program activities with farmer participation. In other conditions, there is a significant direct influence between the environment and socioeconomic with farmer participation. Environmental and socioeconomic aspects influence farmer participation in community empowerment programs. This condition can mean the farmer can express their aspirations and participate. The practical implications of the results of this research can be used to optimize empowerment programs that involve farmers to be independent and implement sustainable farming practices. Reducing the risk of failure that may occur, can also facilitate the performance of agricultural extension workers in delivering programs.